2014
DOI: 10.3109/15513815.2014.959678
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Anomalies of the Kidney and the Urinary Tract (CAKUT)

Abstract: This article reviews the majority of Congenital Anomalies of the Kidney and Urinary Tract (CAKUT) with emphasis in Pediatric Pathology describing and illustrating lesions as varied as ureteral duplications, ureteropelvic junction obstruction, horseshoe kidney, posterior urethral valve and prune belly syndrome, obstructive renal dysplasia, nonmotile ciliopathies and several syndromes associated with renal malformations (Meckel–Joubert, short rib, Bardet–Biedl, asplenia/polysplenia, hereditary renal adysplasia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
112
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(115 citation statements)
references
References 47 publications
(50 reference statements)
2
112
0
1
Order By: Relevance
“…Other authors also observed a regression of renal cysts [13]. However, renal insufficiency occurs in 5-25% of BBS cases, and in 4-10% of cases the insufficiency is progressive, which is the most frequent cause of death [14,15].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other authors also observed a regression of renal cysts [13]. However, renal insufficiency occurs in 5-25% of BBS cases, and in 4-10% of cases the insufficiency is progressive, which is the most frequent cause of death [14,15].…”
Section: Discussionmentioning
confidence: 98%
“…Diagnosis of this syndrome is based mostly on clinical criteria and, due to a better prognosis, requires a priori exclusion of BBS [6,15]. One of the known genes responsible for this syndrome is the MKS gene.…”
Section: Discussionmentioning
confidence: 99%
“…Many theories exist to explain the development of intrinsic UPJO. Some authors postulate that intrinsic UPJO is thought to be a result of inadequate recanalization in utero at 10-12 weeks of gestation [1] and others associate it with smooth muscle cell apoptosis and defective neural development [3].…”
Section: Discussionmentioning
confidence: 99%
“…[2] CAKUT includes a wide range of kidney anomalies including aplasia, hypoplasia, adysplasia, multicystic dysplasia and ureteric anomalies such as megaureter, ureteropelvic junction obstruction or incompetence, duplex kidney/ureters, and anomalies of the bladder and urethra. [3,4] Renal adysplasia is rare, occurring in only one per 10,000 births. Despite its being moreover a sporadic event, there is a M:F ratio of 2.5 to 1 and approximately 20-36% present with a familial recurrence, probably autosomal dominant mode of inheritance with incomplete penetrance and variable expression, termed as hereditary renal adysplasia.…”
Section: Discussionmentioning
confidence: 99%